Resenha do livro : Bancel Nicolas et al., La fracture coloniale . La société française au prisme de l'héritage colonial, Paris, La Découverte « Cahiers libres », 2005, 322 páginas. - CARLA TOMAZI (Geografares, 2014)
This collective book, coordinated by Pascal Blanchard, Nicolas Bancel and Sandrine Lemaire, presents essays on the effects of the “colonial fact” on contemporary France by scholars from various disciplines. The central question addressed in this article concerns the impact of French colonization in the metropolis, and the fact that independence of colonies have not necessarily led to a rupture between the colonial and postcolonial period. The “colonial fracture” occurs within the borders of France itself. This is the reason why the object of the book is “France as a postcolonial society”